Learn Today-Apply Tomorrow: The SMART Pharmacist Program - Michael J Rouse; Arijana Meštrović (MDPI AG, 2020)
The SMART Pharmacist Program was initiated by the Accreditation Council for Pharmacy Education (ACPE) and Pharma Expert in 2014. It was designed to introduce a new continuing education model for pharmacists for the Turkish Pharmacists' Association, and to support development of competencies for future practice. After successful implementation in Turkey, the Program spread to 16 additional countries. To assure quality, globally adopted and validated tools and best practices were used, respecting the national context. National competency frameworks and quality indicators for pharmaceutical care delivery were developed. Pharmacists' learning portfolios were introduced and patient care modules created. Under the sub-title "Learn Today-Apply Tomorrow," the changes in practice were introduced under the leadership of national host organizations. The Program showed an impact on the patient level in several countries, especially in areas of patient care in Asthma and Chronic Obstructive Pulmonary Disease (COPD), Hypertension and Dyslipidemia, Diabetes, and the patient care process in general (e.g., identifying drug-related problems, improving patient safety, collaborating with medical doctors). Changes are visible at the individual (pharmacists) and organizational levels. Barriers and facilitators to the change-management process during Program implementation are identified. In some countries, the Program is recognized as one of the most important initiatives in pharmacy education and practice, with visible support of national medicines agencies, academia, government, and WHO regional offices.